Prodigiosin purification from Serratia marcescens M10 and its antitumor activities - Luong, Vu Trong; Thanh, Nguyen Sy Le; Tuyen, Do Thi; Cuc, Do Thi; Thao, Do Thi (Vietnam Journal of Biotechnology, 2021)
Prodigiosin (Pg) is a bright red pigment, which is produced by gram negative and gram positive bacteria including Serratia marcescens, Hahella chejuensis, Vibrio psychroerythrus, Streptomyces coelicolor and many other marine bacteria such as Pseudomonas sp., Vibrio sp. Pg induces apoptosis in different kinds of cancer cells with low toxicity on normal cells. In this study, we purified Pg from solid fermentation of S. marcescens M10 strain and assessed its anticancer activity in tumorized mice. The results showed that Pg was purified by running through a silicagel 60 column with a suitable solvent system of n-hexane:toluene at the rate of 1:1 (v/v) combined with toluene:ethyl acetate at the rate of 9:1 (v/v). TLC plate was used to test the presence of active substances with separation solvent n-hexane:ethyl acetate ratio of 1:1 (v/v). The purity of fractions tested by high performance liquid chromatography method showed as 98%. Purified fractions also showed promising anti-tumor activity in Lewis lung carcinoma induced tumors in BALB/c mice. The tumor volumes in Pg treated groups decreased by 34.18% after 28 days of administration.